2017
DOI: 10.1038/ncomms15715
|View full text |Cite
|
Sign up to set email alerts
|

Giant barocaloric effect in the ferroic organic-inorganic hybrid [TPrA][Mn(dca)3] perovskite under easily accessible pressures

Abstract: The fast growing family of organic–inorganic hybrid compounds has recently been attracting increased attention owing to the remarkable functional properties (magnetic, multiferroic, optoelectronic, photovoltaic) displayed by some of its members. Here we show that these compounds can also have great potential in the until now unexplored field of solid-state cooling by presenting giant barocaloric effects near room temperature already under easily accessible pressures in the hybrid perovskite [TPrA][Mn(dca)3] (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
102
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(109 citation statements)
references
References 57 publications
3
102
0
4
Order By: Relevance
“…To date, giant BC effects have only been experimentally demonstrated near room temperature in a polymer 10 , a small number of relatively expensive magnetic materials 11 16 , a number of fluorites 17 20 , a hybrid perovskite 21 and a small number of ferro/ferrielectric materials 22 , 23 . Following the recent prediction of giant BC effects in fluoride-based superionic conductors at very high temperatures 24 , we demonstrate here giant BC effects nearer to room temperature in a powder of AgI, which is the prototypical solid electrolyte that was shown to display fast ionic conduction over one century ago 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, giant BC effects have only been experimentally demonstrated near room temperature in a polymer 10 , a small number of relatively expensive magnetic materials 11 16 , a number of fluorites 17 20 , a hybrid perovskite 21 and a small number of ferro/ferrielectric materials 22 , 23 . Following the recent prediction of giant BC effects in fluoride-based superionic conductors at very high temperatures 24 , we demonstrate here giant BC effects nearer to room temperature in a powder of AgI, which is the prototypical solid electrolyte that was shown to display fast ionic conduction over one century ago 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Compounds that combine simultaneously organic and inorganic chemical groups are of great interest since they enlarge the range of structural possibilities that allow the coexistence and modulation of fundamental physical properties, increasing their multifunctional potential [ 1 ]. These hybrid inorganic-organic compounds have attracted great attention in the last years in view of their high technological potential in the areas of optoelectronics [ 2 ], photovoltaics [ 3 ], ferroelectrics [ 4 ], multiferroics [ 5 , 6 ], and, very recently, also in the field of barocaloric materials for solid-state cooling [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A very prominent member of this family is the manganese azide with A: [(CH 3 ) 4 N] + (n = 4), (TMA), (TMAMnN 3 ), the first azide reported to have a three-dimensional framework structure [ 17 ], which is now known to show coexistence of three ferroic orders (antiferroelectric, ferroelastic and magnetic bistability) [ 6 , 16 ]. In addition, in view of its very large entropy change at the ferroelastic phase transition (two times larger than in the case of the giant barocaloric hybrid perovskite [TPrA][Mn(dca) 3 ] (TPrA = (CH 3 CH 2 CH 2 ) 4 N + , dca = [N(CN) 2 ] − ) [ 8 ]), it has been first proposed [ 6 ] and recently experimentally proved that this material is a very promising barocaloric material [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Most extensively studied perovskite-type compounds contained HCOO − ligands but recently those with dicyanamide (N(CN) 2 −, dca) ligands also gained significant interest due to their complicated sequence of phase transitions as well as dielectric, barocaloric, and non-linear optical properties. [9][10][11][12][13][14] In this respect, former studies of tetrapropylammonium manganese dicyanamide (TPrAMn) showed that this compound exhibits only one structural phase transition at 330 K. [10] Further studies of Fe, Ni, and Co analogues revealed that these compounds undergo three structural phase transformations of the same character. [11] It is also worth noting that TPrAMn and TPrACo exhibit very strong pressure dependence of the phase transition temperatures and large phase transition entropies.…”
mentioning
confidence: 99%
“…[10,12] Thus, these compounds were shown to exhibit a large barocaloric effect. [12,14] TPrAM (M¼Mn, Fe, Co, Ni) compounds were studied using X-ray diffraction, thermal, and dielectric methods. [9][10][11] In spite of these studies, phase transition mechanisms of Mn, Fe, Co, and Ni analogues are still not well understood.…”
mentioning
confidence: 99%